Analiza circumstantei speciale de individualizare a pedepsei penale, precum si a clauzei de impunitate consemnate la art.278 din Codul Penal al Republicii Moldova (actul terorist) - Cojocaru, Violeta M. (Iași:Performantica, 2018)
This paper analyzes the special circumstance of individualization the criminal punishment for committing the act of terrorism (in the sense of its mitigation). In this context, are highlighted its particularities, including the conditions under which it becomes operational. It is pointed out the opportunity of such mitigating circumstance in the para.(5) Art.278 of the Criminal Code of the Republic of Moldova. Also it is analyzed the special impunity clause provided by para.(6) Art.278 of the Criminal Code of the Republic of Moldova. There are outlined conditions in whose presence is it applicable. Is performed the delimitation of the so-called impunity clause by the release of criminal liability in connection with the voluntary renunciation of the offense. It is argued that the impunity clause provided by para. (6) Art.278 of the Criminal Code of the Republic of Moldova have the effect of preventing the phenomenon of terrorism.
THE ANALYSIS OF THE SPECIAL CIRCUMSTANCES OF INDIVIDUALIZATION OF CRIMINAL PENALTIES REGARDING THE IMPUNITY CLAUSE REFERRED TO IN ARTICLE 278 OF THE REPUBLIC OF MOLDOVA PENAL CODE: THE ACT OF TERRORISM
Keywords: comparative study; impunity clause; individualization; mitigating circumstance; punishment; terrorism; terrorist act